2021
DOI: 10.3892/etm.2021.10647
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑inflammation treatment for protection of hepatocytes and amelioration of hepatic fibrosis in rats

Abstract: Chronic inflammation is considered as an important pathophysiologic mechanism of hepatic cirrhosis, which induces hepatocyte injury and activates hepatic stellate cells (HSCs), thus resulting in hepatic fibrosis. Previous studies have reported that cyclooxygenase-2 (COX-2) inhibitor can effectively treat liver fibrosis, while somatostatin (SST) analogues inhibit the activation of HSCs. The present study aimed to investigate the effects of a COX-2 inhibitor, celecoxib, combined with a SST analogue, octreotide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Qiu et al [ 16 ] found that HE staining and transmission electron microscopy could be used to observe the occurrence and improvement of liver fibrosis. Feng et al [ 17 ] found that HE staining and transmission electron microscopy could be used to observe the occurrence and improvement of liver fibrosis. And the results of liver histological observation also showed the polysaccharides could make resistance to liver injury induced by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Qiu et al [ 16 ] found that HE staining and transmission electron microscopy could be used to observe the occurrence and improvement of liver fibrosis. Feng et al [ 17 ] found that HE staining and transmission electron microscopy could be used to observe the occurrence and improvement of liver fibrosis. And the results of liver histological observation also showed the polysaccharides could make resistance to liver injury induced by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with rodent models indicated that SST and its analogs protected the liver from injuries caused by several types of stress, such as restraint stress [134], TAA-induced cirrhosis [135], and hepatic-ischemia/reperfusion injury [136]. It was reported that a combination of octreotide (SST analog) and celecoxib (COX-2 inhibitor) attenuated TAA-induced liver damage by reducing HSC activation, hepatic inflammation, and fibrosis [137].…”
Section: Somatostatinmentioning
confidence: 99%
“…Mean amount of liver connective tissue in healthy male Sprague-Dawley rats. Graphs (mean ± two standard errors) of the amount of liver connective tissue quantified on histological sections stained with Masson's trichrome[13,14,19,26,29,30,33,38,54,[56][57][58]63] (a) or picrosirius red[4,13,21,25,27,32,34,36,39,[42][43][44][48][49][50]52,55,58,60,62,64] (b) revealed significant differences. Multiple graphs within one study represents multiple rat groups within the study.…”
mentioning
confidence: 99%